Can one long peritoneal dwell with icodextrin replace two short dwells with glucose? - Stachowska-Pietka, Joanna; Waniewski, Jacek; Olszowska, Anna; Garcia-Lopez, Elvia; Yan, Junfei; Yao, Qiang; Wankowicz, Zofia; Lindholm, Bengt (Frontiers in Physiology, 2024)
Background Due to the slower dissipation of the osmotic gradient, icodextrin-based solutions, compared to glucose-based solutions, can improve water removal. We investigated scenarios where one icodextrin-based long dwell (Extraneal) replaced two glucose-based exchanges. Methods The three-pore model with icodextrin hydrolysis was used for numerical simulations of a single exchange to investigate the impact of different peritoneal dialysis schedules on fluid and solute removal in patients with different peritoneal solute transfer rates (PSTRs). We evaluated water removal (ultrafiltration, UF), absorbed mass of glucose (AbsGluc) and carbohydrates (AbsCHO, for glucose and glucose polymers), ultrafiltration efficiency (UFE = UF/AbsCHO) per exchange, and specified dwell time, and removed solute mass for sodium (ReNa), urea (ReU), and creatinine (ReCr) for a single peritoneal exchange with 7.5% icodextrin (Extraneal®) and glucose-based solutions (1.36% and 2.27%) and various dwell durations in patients with fast and average PSTRs. Results Introducing 7.5% icodextrin for the long dwell to replace one of three or four glucose-based exchanges per day leads to increased fluid and solute removal and higher UF efficiency for studied transport groups. Replacing two glucose-based exchanges with one icodextrin exchange provides higher or similar water removal and higher daily sodium removal but slightly lower daily removal of urea and creatinine, irrespective of the transport type present in the case of reference prescription with three and four daily exchanges. Conclusion One 7.5% icodextrin can replace two glucose solutions. Unlike glucose-based solutions, it resulted only in minor differences between PSTR groups in terms of water and solute removal with UFE remaining stable up to 16 h.